Coronary calcifications, the Achilles heel in coronary interventions - Dawood, Moustafa; Elwany, Moustafa; Abdelgawad, Hoda; Sanhoury, Mohamed; Zaki, Moataz; Elsharkawy, Eman; Nawar, Moustafa (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2024)
Percutaneous coronary intervention in severely calcified coronaries has been associated with higher rates of procedural complications, including myocardial infarction and death in addition to increased frequency of coronary revascularization on an intermediate and long-term basis. The SYNTAX score, which is designed to assess the complexity of coronary artery disease and aids in choosing a revascularization method, allocates two points per lesion when there is heavy calcification present on fluoroscopy. With the advent of novel multimodality imaging technologies, the detection and evaluation of coronary calcifications improved significantly over the last decade. Several tools are now available for modifying calcified lesions including different types of dedicated balloons and atherectomy devices, which may create some degree of confusion regarding the suitable application of each instrument. The aim of this review is to cover this vital topic from different aspects. First, we tried to provide an overview on the pathophysiology and types of coronary calcification and its risk factors. Then, we outlined the available imaging modalities for the evaluation of calcified coronary lesions, highlighting the points of strength and weakness of each of them. A comprehensive discussion of calcium-modifying techniques was elaborated, summarizing their mechanism of action, pros and cons, and possible complications. Finally, an integrated algorithm was proposed for the best management of calcified coronary lesions.